Analisis dan Perancangan Sistem Informasi Pelaporan Sampah (Studi Kasus pada Dinas Lingkungan Hidup dan Kebersihan Kabupaten Sidoarjo) - Irvan Dwiantono Kartomiharjo; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
One of the tasks of the Sidoarjo Regency's Office of the Environment and Hygiene is to ensure that the Sidoarjo Regency's environment is free of rubbish. The waste problem is one of the main problems in the Department of Environment and Cleanliness of Sidoarjo Regency. For this reason, the role of the community is important in terms of reporting the occurrence of garbage piles so that DLHK can swiftly handle it. At this time the reporting of waste discovery is still done manually where the public must come to DLHK to report so that it takes a long time in the reporting process and it is difficult to know the progress of the community reporting process. For this reason, an information system is needed to deal with the problem. For the information system to match what is needed, a design that analyzes the needs of the community and DLHK is needed. Then the OOAD (Object-Oriented Analysis and Design) approach is used. In the needs analysis phase, 53 functional needs and 1 non-functional needs were generated. At the design stage, UML diagrams are used which produce 22 sequence diagrams, 2 class controller diagrams, 2 class diagram models, physical data models, and 24 user interface designs. Then to evaluate the needs analysis and design made the requirement configuration structure is used which produces a value of 100%. Evaluation also uses the traceability matrix method in which the results explain that all designs are made following with the needs analysis.